Pengaruh Hutang dan Modal Kerja terhadap Profitabilitas - Kodey, Devi Kristianingsih; Rosita, Siti Ita; Sari, Ervina Indri (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
The purpose of this study is to determine whether there is an influence of debts and working capital on profitability in retail trade sub sector companies listed on the Indonesia Stock Exchange in 2014-2018. The population and sample used in this study are 21 retail trade sub-sector companies listed on the Indonesia Stock Exchange in 2014-2018. The research method used is descriptive using secondary data. The statistical analysis used in this study is the classic assumption test, multiple linear regression analysis, coefficient of determination test, and hypothesis testing using t test and F test. The results of the research indicate that partially, debt has a significant effect on profitability, while working capital has no significant effect on profitability. Debts and working capital simultaneously have significant effects on profitability. In addition, the results of the coefficient of determination test show the Adjusted R Square value of 0.125. Debts and working capital have an influence on profitability for 12.5% ​​and the remaining 87.5% is influenced by other variables that were not examined. Keywords: Debts, Working Capital, and Profitability